MANAJEMEN PONDOK PESANTREN DALAM MEMBINA PERILAKU RELIGIUS SANTRI - Sobarie, Nur (ASCENT: Al-Bahjah Journal of Islamic Education Management, 2023)
This study aims to determine the extent to which pesantren management produces religious students at the Tahfidz Al-Bahjah Islamic Boarding School, this research uses a descriptive qualitative approach. Qualitative data were obtained from interviews, observations, and documentation which were then processed descriptively. Religious behavior is one aspect of human personality that cannot stand alone, meaning that religious abilities are not formed by themselves. Research on the management of Islamic boarding schools in fostering the behavior of students is the focus of research to examine the application of religious behavior practices such as carrying out daily activities such as Ubudiyah which are carried out consistently such as praying at midnight, wirid, reading the Qur'an, and practicing other sunnahs. as well as examining the problem of students who cannot behave religiously. The results in this study show that a plan is made programmatically, starting from daily worship activities, Dars students, and applying the boarding school rules book to make students behave religiously, while the inhibiting factors include young administrators making lack of istiqomah control in daily activities so that supervision in fostering religious behavior is carried out directly from the head of the Islamic boarding school, the head of the Riayah, even the Pangasuh Buya Yahya directly supervises every day, which is implemented in the Tafaqquh Program at the Al-Bahjah Islamic Boarding School in Sendang Sumber Cirebon.